Exosomes: Potential Biomarkers and Functions in Head and Neck Squamous Cell Carcinoma - Li, Ting; Li, Juan; Wang, Haitao; Zhao, Jiayu; Yan, Mingze; He, Hongjiang; Yu, Shan (Frontiers in Molecular Biosciences, 2022)
Head and neck squamous cell carcinoma (HNSCC), originating from the mucosal epithelial cells of the oral cavity, pharynx, and larynx, is a lethal malignancy of the head and neck. Patients with advanced and recurrent HNSCC have poor outcomes due to limited therapeutic options. Exosomes have active roles in the pathophysiology of tumors and are suggested as a potential therapeutic target of HNSCC. Exosomes in HNSCC have been intensively studied for disease activity, tumor staging, immunosuppression, and therapeutic monitoring. In this review, the biological mechanisms and the recent clinical application of exosomes are highlighted to reveal the potential of exosomes as biomarkers and therapeutic targets for HNSCC.